Perceptions of Covid-19 Vaccines among Students at DEBESMSCAT-Cawayan Campus, Cawayan, Masbate, Philippines - Ibañez Jr., Roger Yatan; Velza, Jacob Frederick Palabiano; Velza, Sheena Joyce Palabiano (Jurnal Kesehatan Masyarakat, 2024)
This study investigated the perceptions of students at DEBESMSCAT Cawayan Campus regarding COVID-19 vaccines. A descriptive survey method was used, and data were collected using a questionnaire. The findings revealed that a majority of the students at DEBESMSCAT Cawayan Campus have received COVID-19 vaccinations, falling short of the targeted vaccination rate of 70% mandated by the Commission on Higher Education (CHED) for the resumption of face-to-face classes. A proportion of unvaccinated students expressed willingness to receive the vaccine. Overall, the COVID-19 vaccine was perceived as a crucial tool in preventing and protecting individuals from the virus, ensuring the safety of students' health in the face of the COVID-19 pandemic. However, a portion of students harbored doubts about the vaccine's efficacy in protecting against the virus. The study identified common reasons behind vaccine hesitancy among students, including fear of potential side effects, lack of trust in the vaccine's safety and effectiveness, and exposure to misinformation about the vaccine. These findings highlight the importance of addressing the concerns of hesitant students through educational initiatives and awareness campaigns that emphasize the benefits of vaccination. Such efforts will play a vital role in promoting vaccine acceptance and ensuring the well-being of students and the broader community in the face of the ongoing pandemic. Further research is warranted to explore the underlying factors influencing students' decision-making processes regarding vaccination.